Atrium Design in Hot and Dry Climates: Understanding the Influence of Achitectural Form Variation on Indoor Thermal Conditions - Khalida Boussebci; Noureddine Zemmouri; Chafik Mahaya (Proceedings of the International Conference of Contemporary Affairs in Architecture and Urbanism-ICCAUA)
The atrium is becoming more prevalent in desert regions as a key architectural and functional element in the urban landscape. In southern Algerian cities, we are observing an increasing integration of centralized atriums in public buildings. However, this integration may have an impact on the indoor environmental conditions of the buildings. This study investigates the influence of architectural aspects on the indoor thermal behavior of an existing centralized and enclosed atrium in the hot and dry climate of Laghouat. The study analyzes the influence of tow parameters, namely height and glazed area ratio, during summer season. The EDSL-Tas software for dynamic thermal simulation modeling was used. The results revealed that the vertical temperature distribution in the atrium varies depending on its design, as a result of incoming solar radiation.